Phylogeny, regeneration, ageing and cancer: role of microenvironment and possibility of its therapeutic manipulation - Smetana, K; Dvořánková, B; Lacina, L (Folia biologica, 2013)
Data about the possible correlation between reduction of the regeneration capacity in the course of phylogeny and formation of malignant tumours have been summarized from invertebrates to mammals. The evolutionarily increasing complexity of body building plane and expectancy of longevity in the course of phylogeny seems to be grossly negatively correlated with diminished regeneration capacity, but positively with increased occurrence of malignant tumours. A certain evolution-based switch-off mechanism reducing the extent of regeneration in developmentally complicated and long-living animals such as mammals and birds can be hypothesized and benefits of loss of this ability are discussed. This high incidence of malignancies seems to be related, in addition to other factors, to prolonged and cumulative exposure to cancerogenic stimuli in the course of lifetime. Longevity, supported by the progress and availability of medical care to the population, has been unveiling this phenomenon during recent decades. From this point of view, ageing represents the main risk for cancer acquisition. The probable role of microenvironment in all the discussed phenomena such as healing/regeneration, inflammation, and cancer is discussed and targeting of microenvironment is consequently predicted as a possible therapeutic target where controlled manipulation may represent a new approach to the treatment of cancer patients.
Keywords: regenerace; nádory; stárnutí; Animals; Humans; Regeneration; lidé; Phylogeny; zvířata; fylogeneze; Aging; Neoplasms